INTEGRATING PRACTICE AND PLAY-SEQUENCE APPROACHES TO FOSTER MOTIVATION AND MOTOR SKILL MASTERY IN ELEMENTARY PHYSICAL EDUCATION - Bernediv Nurdin (Curricula: Journal of Teaching and Learning, 2025)
The development of fundamental motor skills is a cornerstone of physical education in primary schooling and contributes directly to students’ long-term physical, cognitive, and emotional development. However, traditional instruction in motor learning often prioritizes repetitive technical exercises, which may hinder student motivation and engagement. This study explores how integrating the practice method and the play-sequence method can enhance both skill acquisition and learning motivation in elementary physical education classes, particularly in small-ball games. Using a qualitative descriptive design, this study synthesizes theoretical perspectives and empirical findings from prior pedagogical research to analyze how these methods shape motor learning outcomes and affective engagement. The findings indicate that the practice method supports precise technical mastery through structured repetition, while the play-sequence method fosters intrinsic motivation, creativity, and social interaction. When combined, these methods produce synergistic effects that strengthen psychomotor competence and student enthusiasm. The study argues that an integrated pedagogical approach grounded in experiential and motivational learning principles contributes to achieving Sustainable Development Goal 4 (Quality Education) by promoting inclusive, equitable, and effective learning practices.